2022
DOI: 10.3390/polym14214728
|View full text |Cite
|
Sign up to set email alerts
|

Application of Infrared Spectroscopy in Research on Aging of Silicone Rubber in Harsh Environment

Abstract: Polymer insulators using silicone rubber materials as sheds and sheaths are widely used in power systems to replace traditional porcelain and glass insulators which are heavy, inconvenient to install, and prone to pollution flashover. However, in recent years, polymer insulators that have been operating in harsh outdoor environments for many years have experienced different degrees of aging. The aging degree and aging products of silicone rubber are the focus of research. Fourier transform infrared spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…2.3.4 Fourier spectroscopy. Fourier transform infrared spectroscopy (FTIR) utilizes the principle of interference modulation, and is commonly used for vintage testing and analysis of wine products, authenticity identification of honey, and quality testing of cereals, starch 33 and fruits and vegetables. The KBr compression method was used for the determination using a Thermo Fisher Nicolet-iN10 FTIR spectrometer to measure the samples at 20 °C.…”
Section: Papermentioning
confidence: 99%
“…2.3.4 Fourier spectroscopy. Fourier transform infrared spectroscopy (FTIR) utilizes the principle of interference modulation, and is commonly used for vintage testing and analysis of wine products, authenticity identification of honey, and quality testing of cereals, starch 33 and fruits and vegetables. The KBr compression method was used for the determination using a Thermo Fisher Nicolet-iN10 FTIR spectrometer to measure the samples at 20 °C.…”
Section: Papermentioning
confidence: 99%
“…The appearance of both the C─O peak (corresponding to the carboxyl group) at 1279 cm −1 and the Si-C peak at 1258 cm −1 in the Fourier transform infrared spectroscopy of the coated catheter group proved the formation of the hydrogel on the catheter (Figure S3, Supporting Information). [20][21][22] Finally, to prevent ion leakage from the hydrogel, a Poly(vinylidene fluorideco-hexafluoropropylene) (PVDF-HFP) layer was grown outside in situ, where the interface exhibited stable adhesion (Figures S4 and S5, Supporting Information).…”
Section: Fabrication Of the Temperature-sensing Hydrogel Coatingmentioning
confidence: 99%
“…Additionally, Liu et al analyzed the temperature distribution patterns under temperature and pressure loads, which explained the failure of silicone rubber seal structures on barrel hangers in high-pressure and extreme temperature environments, uncovering the reasons for early rubber failure [18]. Considering the aging process of silicone rubber in harsh environments, such as high altitudes and strong salt spray, Zhang et al conducted a detailed study using ATR-FTIR (Attenuated total reflection-Fourier transform infrared) spectroscopy [19]. Their findings indicated that silicone rubber underwent a degree of degradation, with the main polymer chains breaking, and a reduction in polymerization.…”
Section: Introductionmentioning
confidence: 99%